Predictors of malnutrition risk in neurodegenerative diseases: The role of swallowing function. (15th April 2022) - Pizzorni, Nicole; Ciammola, Andrea; Casazza, Giovanni; Ginocchio, Daniela; Bianchi, Federica; Feroldi, Sarah; Poletti, Barbara; Nanetti, Lorenzo; Mariotti, Caterina; Mora, Gabriele; Schindler, Antonio
Abstract: Background and purpose: Oropharyngeal dysphagia is generally recognized to increase the risk of malnutrition; however, its role in patients with neurodegenerative disease has yet to be determined. This cross‐sectional study aimed to investigate the impact of swallowing function on malnutrition risk in patients with neurodegenerative diseases. Methods: Patients with oral nutrition and diagnosis of Huntington disease (HD), Parkinson disease (PD), or amyotrophic lateral sclerosis (ALS) were recruited. Demographic and clinical data were collected. The swallowing assessment included a fiberoptic endoscopic evaluation of swallowing, an oral phase assessment, and a meal observation scored with the Mealtime Assessment Scale (MAS). Malnutrition risk was assessed with the Mini Nutritional Assessment. Results: Overall, 148 patients were recruited (54 HD, 33 PD, and 61 ALS). One hundred (67.6%) patients were considered at risk of malnutrition. In the multivariate analysis, age ≥ 65 years (odds ratio [OR] = 3.16, p  = 0.014), disease severity (moderate vs mild OR = 3.89, severe vs mild OR = 9.71, p  = 0.003), number of masticatory cycles (OR = 1.03, p  = 0.044), and MAS safety (OR = 1.44, p  = 0.016) were significantly associated with malnutrition risk. Conclusions: Prolonged oral phase and signs of impaired swallowing safety during meals, together with older age and disease severity, are independent predictors of malnutrition risk in neurodegenerative diseases. This study broadens the focus on dysphagia, stressing the importance of early detection not only of pharyngeal signs, but also of oral phase impairment and meal difficulties through a multidimensional swallowing assessment. Abstract : The association between malnutrition risk and swallowing function was investigated in three neurodegenerative diseases (Parkinson disease, Huntington disease, and amyotrophic lateral sclerosis). A prolonged oral phase and signs of impaired swallowing safety during meals, together with older age and disease severity, were found to be independent predictors of malnutrition risk in neurodegenerative diseases. Thus, a multidimensional swallowing assessment, including an evaluation of the oral and the pharyngeal phases of swallowing and a meal observation, is recommended to estimate dysphagia‐related pulmonary and nutritional risk.